2022
DOI: 10.3389/fped.2022.936813
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between diabetes mellitus and attention deficit hyperactivity disorder: A systematic review and meta-analysis

Abstract: BackgroundThis study aims to investigate the prevalence estimate of diabetes mellitus (DM) among people with attention deficit hyperactivity disorder (ADHD) as well as the prevalence of ADHD among those with DM. In addition, the impact of ADHD on glycemic control in patients with DM was also assessed using a systematic review and meta-analysis of currently available published data.Materials and methodsThe PubMed, Embase, Web of Science, and PsycInfo databases were searched for potential studies. Two reviewers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Consistent with our results, both T2DM and hypertension were more common in men than in women with ADHD in the Swedish study. The prevalence of T2DM in patients with ADHD in a pooled analysis of five studies was higher than that in the control population (OR: 2.05, 95% CI: 1.37, 3.07, I 2 = 92%, p <0.01) ( 16 ). Moreover, a Taiwanese study showed a higher incidence of T2DM in young adults with ADHD ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with our results, both T2DM and hypertension were more common in men than in women with ADHD in the Swedish study. The prevalence of T2DM in patients with ADHD in a pooled analysis of five studies was higher than that in the control population (OR: 2.05, 95% CI: 1.37, 3.07, I 2 = 92%, p <0.01) ( 16 ). Moreover, a Taiwanese study showed a higher incidence of T2DM in young adults with ADHD ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified a possible link between ADHD and non-psychiatric disorders ( 10 ), including cardiovascular disease (CVD) ( 11 ), atopic dermatitis ( 12 , 13 ), and gout ( 14 ). The health-risk behavior exhibited by patients as a result of ADHD-associated symptoms and deficits along with a common underlying pathophysiology ( 15 ) may increase the risk of comorbidities, such as diabetes mellitus ( 4 , 16 18 ), dyslipidemia ( 11 ), and hyperuricemia ( 14 ), in patients with ADHD. Moreover, a strong association between ADHD and nervous system disorders and respiratory, musculoskeletal, and metabolic diseases has been reported in a Swedish registry study ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral glucose hypometabolism has been found in childhood-onset adult ADHD patients ( Zametkin et al, 1990 ), however, this may also be a consequence of deficits in impulse control leading to metabolic syndrome ( di Girolamo et al, 2022 ). Indeed, a recent meta-analysis found a bidirectional association between ADHD and T2DM ( Ai et al, 2022 ), pointing to long-lasting BIR effects. Interestingly, some significant genetic correlations with insulin-related phenotypes were found for ADHD and AD that provide the foundations for the hypothesis of insulinopathies in the brains of such disorders ( Fanelli et al, 2022 ).…”
Section: Attention-deficit Hyperactivity Disorder Current Genetic And...mentioning
confidence: 99%
“…In particular, comorbid psychological and neurodevelopmental disorders were shown to impair diabetes management 5–8. A prime example is attention deficit hyperactivity disorder (ADHD), which affects 5%–10% of children9 and is reported to be up to 35% more frequent (OR 1.35; 95% CI 1.08 to 1.73) in patients with T1D compared with healthy peers 10. A Swedish active screening of children with T1D showed that among children with newly diagnosed ADHD, 77.8% had inadequate metabolic control (mean HbA1c >8.6%) compared with 42.9% in the group of children with treated ADHD 11.…”
Section: Introductionmentioning
confidence: 99%
“… 11 Association between ADHD and poor T1D control was also reported by German and Israeli studies. 12 13 In addition, those patients experience an elevated risk of life-threatening episodes of severe hypoglycaemia or ketoacidosis, resulting in prolonged hospitalisations 10 14 15 and long-term complications, such as diabetic nephropathy. 5 From that perspective, the need for evidence regarding the effectiveness and safety of ADHD treatment in paediatric T1D emerges as a pertinent clinical challenge.…”
Section: Introductionmentioning
confidence: 99%